BEBERAPA ASPEK PENGELUARAN KAYU DARI AREAL KONVERSI UNTUK BAHAN BAKU INDUSTRI DI SUMATERASELATAN - lsmatul Hakim; Kirsfianti Linda; Hariyatoo Dwiprabowo (Jurnal Penelitian Hasil Hutan (Journal of Forest Products Research), 2017)
Conversion forests in Indonesia whida are pardy still virgin account for about 41.2 % of the total forest areas. The conversion is needed because of the exlensification of  land for fanning, transmigration, and the exlension of urban area. Pre.senJly, the  information on wood polential from   this forest is scanty. This information is needed to know the possible Ulilization of the logs.